PENGARUH PENAMBAHAN BATU GRANIT DAN RAMBUT SEBAGAI FILLER TERHADAP KUAT TEKAN DAN LENTUR BETON - Mardiaman; Ahmad Fadly; Indriasari (UKI Press, 2022)
Concrete is a mixture consisting of fine aggregate, coarse aggregate, water, cement, and with or without other additives. This research uses a mixture of concrete with hair waste and granite, where the amount of hair waste produced every day from thousands of barbershops in Indonesia is increasing rapidly. The innovation of granite shard waste in the construction of this building is to utilize the waste of granite shards leftover from construction. This study aimed to determine the effect of using granite and hair as a filler on the compressive strength of concrete and the flexural strength of concrete. The time in this study for 35 days was tested for concrete aged 7,14,21,28 and 28 days. With a variation of 0%, 2.5%; 7.5%; 12.5%; 17.5% and 22.5%. The results of this study found that comparing the compressive strength of normal concrete with mixed concrete in the 35-day old concrete test for normal concrete was 321.1 kg/cm2 while for mixed concrete was 305.7 kg/cm2. For comparing the flexural strength of normal concrete with mixed concrete in the 35-day old concrete test, for normal concrete, it is 32 kg/cm2, while for mixed concrete, it is 31.3 kg/cm2. It turns out that the compressive and flexural strength of concrete by adding granite and hair with certain variations to the mixture is still lower than normal co